2005
DOI: 10.4088/jcp.v66n0813
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Remission After Electroconvulsive Therapy in Unipolar Major Depression

Abstract: Context: Electroconvulsive therapy (ECT) is the most effective biological treatment for major depression. However, there is little agreement about clinically useful predictors of acute ECT outcomes. Objective: To assess whether age, sex, burden of comorbid physical illness, age at onset, history of recurrence, episode duration, chronic depression or comorbid dysthymia, melancholic features, episode severity, and medication resistance are predictors of remission after an acute course of ECT. Design: We performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(40 citation statements)
references
References 37 publications
3
34
1
2
Order By: Relevance
“…It is difficult to explain why some earlier smaller studies have reported less positive outcome in patients with psychotic depression [8,9]. However, the result from this study is robust and the reported responder rate in psychotic depression is very high.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…It is difficult to explain why some earlier smaller studies have reported less positive outcome in patients with psychotic depression [8,9]. However, the result from this study is robust and the reported responder rate in psychotic depression is very high.…”
Section: Discussioncontrasting
confidence: 47%
“…Presence of psychotic symptoms[3,6], lower degree of prior treatment resistance [7-9] and shorter symptom duration [8,10] are relatively well established predictors of response to ECT [11]. In addition, the CORE group reported depression in old age to be associated with a favorable outcome [12].…”
Section: Introductionmentioning
confidence: 99%
“…2,44 Studies examining speed of response have generally found that patients with bipolar depression showed a more rapid response and required fewer ECT treatments than patients with MDD 1,3,45,46 In the present study, the association of remission with shorter length of the depressive episode is consistent with previous reports that a longer duration of depression predicted a lower response rate to ECT. [47][48][49][50] From our study, it is not possible to infer whether some patients are intrinsically resistant to treatment and have prolonged episodes for that reason or whether ineffective treatments, in prolonging the episode, contribute to an active process that makes patients difficult to treat. 51 Number of lifetime days spent in depression has been associated with the degree of hippocampal atrophy, implicating an active degenerative process.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most important observation for prescribers is that a failure of patients with depression to recover with a selective serotonin reuptake inhibitor or a monoamine oxidase inhibitor has no bearing on the probability of remission with subsequent ECT. In contrast, a failure to recover with a tricyclic antidepressant drug or bupropion reduces the probability of recovery with subsequent ECT; nevertheless, a half of such patients will recover with ECT (Dombrovski 2005).…”
Section: Beyond the Monoamine Hypothesismentioning
confidence: 99%